(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article examines the importance of pronunciation in English as a Foreign Language (EFL) learning and provides an in-depth analysis of methods, principles, and instructional strategies for developing pronunciation skills. It discusses segmental and suprasegmental features of English, explores pedagogical approaches, and highlights common learner difficulties. The article also presents practical classroom techniques and outlines the teacher’s role in supporting learners’ intelligibility and communicative competence. Recommendations for effective instruction are provided, based on contemporary research in second language acquisition and phonology.